EFEKTIVITAS PENGEMBALIAN BERKAS REKAM MEDIS RAWAT INAP DALAM MENUNJANG KUALITAS LAPORAN DI RUMAH SAKIT BHAYANGKARA SARTIKA ASIH BANDUNG - Alif Kurnia Putri; Dina Sonia (Sekolah Tinggi Pariwisata Mataram, 2021)
The medical record file in a hospital is one that affect the quality of reports in the medical record unit. The return of medical record files that are not timely calculated from the timet the patient returns home results in delays in data processing, reporting, insurance claims and delays in service to patients. The purpose of this study was to determine the return of medical record files in supporting the quality of reports and the level of delay in medical record files.The method used is descriptive method. Method of data collection is done by observasion, interviews and documentation studies. The result of the study show that there are still frequent delays in returning inpatient medical record files. The delay is caused by the doctor’s indiscipline in filling out the form which causes data proccessing and report quality to be ineffective.